PERANCANGAN SISTEM PEMBAYARAN BERBASIS RADIO FREQUENCY IDENTIFICATION (RFID) PADA FOOD COURT - Henky Vasko P. Manalu . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2015)
ABSTRACT Technology based payment system named radio frequency identification (RFID) made as a replacement for payment system on Ayani Mega Mall which it is still manually-operationed. This manual system considered lack on effectiveness in timing use so it makes long queue when customer will pay at cashier. RFID is an identified method using radio wave as transmission media in detecting data. With RFID, the payment will be more efficient so it need less time than manual. RFID consist of two tools, which are transponder/tag and reader, on this system every costumer has different tag and id number. Every tag has registered on database system on software; software is important on this system. The data on this application consist of data of the tag owner and customer balance. This payment system application using Delphi 7.0, the data is taken from database when doing payment. Customer just asked to put the tag near to the reader, so the reader will detect data on tag. It just need about 5,5 centimeters between tag and reader, if more than 5,5 cm, the reader could not detect tag. RFID reader has 13,56 MHz for its radio wave frequency. Keyword : RFID, Auto Id, Technology, Payment System, Food Court